Paragangliomas of the head and neck: clinical, morphological and immunohistochemical aspects - Andrade Filho, Pedro de Alcântara de; Rapoport, Abrão; Alves, Venâncio Avancini Ferreira; Denardin, Odilon Victor Porto; Sobrinho, Josias de Andrade; Carvalho, Marcos Brasilino de (São Paulo Medical Journal, 2001)
CONTEXT: Protein marker positivity can assist in the definition of the therapeutic approach towards head and neck paragangliomas. The establishment of the therapeutic approach should incorporate the results of such an investigation. OBJECTIVE: To establish criteria for benignancy and malignancy of vagal and jugular-tympanic paragangliomas, via the study of the relationships of sex, age, tumor size, duration of complaints, site, family history, presence of metastases, treatment, histological architecture and cell type with the immunohistochemical reactions to S100 protein, chromogranin and AgKi67. DESIGN: A retrospective study of histological and clinical records. SETTING: The Heliópolis and Oswaldo Cruz tertiary general hospitals, São Paulo. SAMPLE: 8 cases of head and neck paragangliomas. MAIN MEASUREMENTS: Determination of degree of positivity to paragangliomas via immunohistochemical reactions. RESULTS: 1). The protein markers for the principal cells (AgKi67 and chromogranin) were sensitive in 100% of the tumors when used together. 2). S100 protein was well identified in the cytoplasm and nucleus of sustentacular cells and underwent reduction in the neoplasias. CONCLUSIONS: Chromogranin was proven to be a generic marker for neuroendocrine tumors; S100 protein was positive in all 8 cases and the AgKi67 had low positivity in all cases.